Zoneamento urbano da praia do Abaís, Estância/SE - Silva, Rayane de Oliveira (2019)
Coastal areas offer a big number of advantages from the economic, social and environmental point of view, so they are target of many occupations that have formed solidified urban areas, aggravating adverse impacts and hampering the public agencies‟ work in attempting to regularize these occupations. Abaís Beach, politically belonging to the Estância city and located on the southern coast of Sergipe, has an occupation history without planning, is a strong tourist pole and has areas that, according to the legislations, should be environmentally protected, such as beach, dunes and lagoon. The main objective of this work is to elaborate an urban zoning for this beach and for that, it was specifically necessary to make a cadastral mapping of use and occupation urban land, a landscape units mapping and a socio-spatial analysis of the area. To this, bibliographical, field and documentary research were done, including interviews with the local community, tourists and managers, and a drone aero photogrammetric survey that enabled the elaboration of the updated maps and the quantitative data collection. The results showed a higher incidence of second residences, among the urban land occupation categories that were identified, a low number of fixed residences, and the lack of public spaces and institutional buildings. In addition, the unoccupied areas appeared prominently, allowing the natural landscape units delimitation, such as sea terraces, dunes, lagoon and wetlands, all these important for the coastal dynamics maintenance. As complementary data source, the socio-spatial analysis of the area raised the visitors, residents, merchants and regulators as the main social actors and highlighted the summer activity, associated with rest and searches for destination on weekends or holidays. These data guided the functional zoning proposal for the area, in which were delimitated, in accordance with the pertinent legislation, the Permanent Preservation Areas, which should be kept free of occupation, are defined in contrast to the Urban Consolidation Zone, which considers a pre-existing and consolidated urban area. In addition, in order to control the urban densification on landscape units, it was suggested strategic zones, as Rare Occupation Zones and Basic Ground Zones. The results of this study will be useful to the community and can serve as a tool to the government agencies in the search of regularize the occupations, minimizing negative environmental impacts, in an attempt to find a balanced relationship between society, economy and the environment.